Complex Perineal Trauma with Anorectal Avulsion - Adelina Maria Cruceru; Ionut Negoi; Sorin Paun; Sorin Hostiuc; Ruxandra Irina Negoi; Mircea Beuran (Case Reports in Surgery)
Introduction. The objective of this case report is to illustrate a severe perineal impalement injury, associated with anorectal avulsion and hemorrhagic shock. Results. A 32-year-old male patient was referred to our hospital for an impalement perineal trauma, associated with complex pelvic fracture and massive perineal soft tissue destruction and anorectal avulsion. On arrival, the systolic blood pressure was 85 mm Hg and the hemoglobin was 7.1 g/dL. The patient was transported to the operating room, and perineal lavage, hemostasis, and repacking were performed. After 12 hours in the Intensive Care Unit, the abdominal ultrasonography revealed free peritoneal fluid. We decided emergency laparotomy, and massive hemoperitoneum due to intraperitoneal rupture of pelvic hematoma was confirmed. Pelvic packing controlled the ongoing diffuse bleeding. After 48 hours, the relaparotomy with packs removal and loop sigmoid colostomy was performed. The postoperative course was progressive favorable, with discharge after 70 days and colostomy closure after four months, with no long-term complications. Conclusions. Severe perineal injuries are associated with significant morbidity and mortality. Their management in high volume centers, with experience in colorectal and trauma surgery, allocating significant human and material resources, decreases the early mortality and long-term complications, offering the best quality of life for patients.